A human leukocyte antigen imputation study uncovers possible genetic interplay between gut inflammatory processes and autism spectrum disorders - Lombardi, Laura; Le Clerc, Sigrid; Wu, Ching-Lien; Bouassida, Jihène; Boukouaci, Wahid; Sugusabesan, Sobika; Richard, Jean-Romain; Lajnef, Mohamed; Tison, Maxime; Le Corvoisier, Philippe; Barau, Caroline; Banaschewski, Tobias; et al. (Translational Psychiatry, 2023)
Autism spectrum disorders (ASD) are neurodevelopmental conditions that are for subsets of individuals, underpinned by dysregulated immune processes, including inflammation, autoimmunity, and dysbiosis. Consequently, the major histocompatibility complex (MHC)-hosted human leukocyte antigen (HLA) has been implicated in ASD risk, although seldom investigated. By utilizing a GWAS performed by the EU-AIMS consortium (LEAP cohort), we compared HLA and MHC genetic variants, single nucleotide polymorphisms (SNP), and haplotypes in ASD individuals, versus typically developing controls. We uncovered six SNPs, namely rs9268528, rs9268542, rs9268556, rs14004, rs9268557, and rs8084 that crossed the Bonferroni threshold, which form the underpinnings of 3 independent genetic pathways/blocks that differentially associate with ASD. Block 1 (rs9268528-G, rs9268542-G, rs9268556-C, and rs14004-A) afforded protection against ASD development, whilst the two remaining blocks, namely rs9268557-T, and rs8084-A, associated with heightened risk. rs8084 and rs14004 mapped to the HLA‐DRA gene, whilst the four other SNPs located in the BTNL2 locus. Different combinations amongst BTNL2 SNPs and HLA amino acid variants or classical alleles were found either to afford protection from or contribute to ASD risk, indicating a genetic interplay between BTNL2 and HLA. Interestingly, the detected variants had transcriptional and/or quantitative traits loci implications. As BTNL2 modulates gastrointestinal homeostasis and the identified HLA alleles regulate the gastrointestinal tract in celiac disease, it is proposed that the data on ASD risk may be linked to genetically regulated gut inflammatory processes. These findings might have implications for the prevention and treatment of ASD, via the targeting of gut-related processes.
Gesehen am 29.08.2023